The gene mutations and subtelomeric DNA methylation in immunodeficiency, centromeric instability and facial anomalies syndrome. (18th August 2019) - Hu, Haochang; Chen, Chujia; Shi, Shanping; Li, Bin; Duan, Shiwei
Abstract: Immunodeficiency, centromeric instability and facial anomalies syndrome (ICF) is a rare autosomal recessive disorder, which is characteristic of a severe impairment of immunity. In the genetic aspect, ICF is featured with mutations primarily located in the specific genes ( DNMT3B for ICF1, ZBTB24 for ICF2, CDCA7 for ICF3, and HELLS for ICF4). The subtelomeric region is defined as 500 kb at the terminal of each autosomal arm. And subtelomeric DNA fragments can partially regulate key biological activities, including chromosome movement and localization in the nucleus. In this review, we updated and summarized gene mutations in ICF based on the previous review. In addition, we focused on the correlation between subtelomeric DNA methylation and ICF. The relationship between subtelomeric methylation and telomere length in ICF was also summarized.